Particle characterization and size analysis - Balog, Eva Rose M. (Henry Stewart Talks, 2024)
Particle characterization, Types of particles, Nanotechnology, Colloids, Particle size distribution statistics, Particle characterization techniques, Light microscopy, Optical microscopy, Light obscuration, Static Light Scattering (SLS) and Dynamic Light Scattering (DLS), Zeta potential, Coulter counting, Atomic Force Microscopy (AFM), Advanced microscopy techniques